Urgensi Kontrak Perdagangan E-Commerce Dalam Hukum Perjanjian - Salamiah Salamiah; Ningrum Ambarsari (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to determine the urgency of trade contracts via the Internet (e-commerce) in terms of contract law in Indonesia and the solutions for problems in implementing trade via the Internet (e-commerce). Using normative research methods, it can be concluded: 1. The agreement applies as a law for the parties who make it, meaning that the parties must comply with the agreement they made the same as obeying the law. As stated in 1320 BW, the legal terms of an agreement are essential (urgency), if the terms of the agreement are not fulfilled, then the agreement is considered null and void by law, both conventional and online, as in e-commerce agreements, 2. The presence of the Internet has changed people's perspective on shopping activities, where shopping can be done both conventionally and online through buying and selling platforms on the Internet (e-commerce). However, some things must be considered when shopping online, including additional costs, product quality, digital payments, security, and sending and returning goods. And if there are problems in implementing trade via the Internet (e-commerce), they can be resolved through two events: Litigation and non-Litigation.